Portrait of a learning organization: Stories from early adopters - Victoria J. Marsick; Karen E. Watkins; Judy O'Neil; Nancy Dixon; Ralph Catalanello (Adult Education Research Conference, 1994)
This article tells the stories of selected learning organizations. The authors first describe their research and lay out a set of four lenses by which to understand organizational learning theories: experiential, structural, informating, and cultural. They then examine the way in which the researched companies positioned their initiatives, built the new capacity, implemented their strategies, and transferred learning within the company. The authors conclude by tying these findings back to their conceptual framework and by discussing implications for practice and for the use of this conceptual framework.